Pendekatan Thread Untuk Reduksi Delay Pada Perangkat Lunak Kendali Ventilator - Lawalata, Sanga; Lareno, Bambang; Sugiarto, Hendrik S. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The ventilator must be able to supply oxygen according to the duration and amount required, not more or less. To produce the expected oxygen levels, air pressure and air flow, all these stages and processes are controlled electronically through software. However, in its development, the software to control ventilator often encounter delay problems. One of them is related to the work of the alarm. Therefore, futher investigation is needed to reduce the delay. In this research, thread concept approach is proposed.  In this approach, the synchronous process is pushed to an asynchronous thread with a non-blocking process, in which the main running process is not blocked. As a result, the delay time decreased significantly, by 98.24% on the average value